1984
DOI: 10.3109/00207458409089803
|View full text |Cite
|
Sign up to set email alerts
|

Pain Threshold Changes in Rats Following Central Injection of Beta-Endorphin, Met-Enkephalin, Vasopressin or Oxytocin Antisera

Abstract: Both opioid peptides such as beta-endorphin and met-enkephalin and nonopioid peptides such as vasopressin and oxytocin increase pain thresholds in rodents. Antisera raised against each of these peptides have been developed for use in immunocytochemical and radioimmunoassay procedures. The present study assessed whether central administration of antisera raised against beta-endorphin (ABE), met-enkephalin (AME), arginine, vasopressin (AAVP) or oxytocin (AOT) altered tail-flick latencies elicited by three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In contrast to the current human study, in animal studies vasopressin has proved effective in suppressing presumably pain-related responses (Berkowitz & Sherman 1982;Berntson & Berson 1980;Berson et a/. 1983;Bodnar et al 1980Bodnar et al & 1984Kordower et al 1982). Species differences may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In contrast to the current human study, in animal studies vasopressin has proved effective in suppressing presumably pain-related responses (Berkowitz & Sherman 1982;Berntson & Berson 1980;Berson et a/. 1983;Bodnar et al 1980Bodnar et al & 1984Kordower et al 1982). Species differences may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 61%
“…There remains the possibility that the application of vasopressin directly to the central nervous system had produced analgesia in our subjects. In some animal studies demonstrating a vasopressin-induced analgesia, intrathecal administration was used (Bodnar et al 1984;Berntson & Berson 1980;Kordower et a/. 1982), although systemic administration has proved effective too (Berson et al 1983;Berntson & Berson 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of AVP is synthesized in hypothalamic paraventricular nucleus (PVN) and hypothalamic supraoptic nucleus (SON) [2,15]. It has been proven that PVN and SON play an important role in analgesia [16][17][18][19][20], and AVP, which may be from PVN and SON, is involved in pain modulation [21,22]. Our present study showed that (1) not only V 1 recep- Histological study has shown that there are many AVP containing fibers in the periaqueductal gray (PAG), which come from PVN neurons [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there have been contradictory reports suggesting that the oxytocin-induced analgesia in rodents is an epiphenomenon accompanying a concomitant seizure 3,6) . A direct analgesic role for oxytocin has also been doubted since lesions of the paraventricular nuclei have no effects on nociception 7) .…”
Section: Introductionmentioning
confidence: 99%